The Recurrent Characteristics of Historic Buildings as a Support to Improve their Energy Performances: The Case Study of Palermo. (March 2017) - Genova, Enrico; Fatta, Giovanni; Vinci, Calogero
Abstract: The analysis of the recurrent characteristics of the local historic architecture is useful to develop large-scale energy analyses, regulations and financial strategies, but also to support technical guidelines for an energy improvement balanced with conservation. For this purpose, a multi-scale methodology ranging from envelope components to the urban dimension is necessary. In the research here exposed, this approach is investigated by focusing on the historic architecture of Palermo. For this heritage, the collection of thermal and hygrometric data for envelope components is combined with the examination of representative constructions, based on building stock categorization. Intended as a contribution to the overall energy analysis of the architectural heritage of Palermo, this case study shows that examining the recurrent characteristics of historic architecture in a local context may promote energy improvements compatible with the material and aesthetic conservation of historic buildings.